Information propagation on cyber, relational and physical spaces about covid-19 vaccine: Using social media and splatial framework. (December 2022) - Yin, Fuzhen; Crooks, Andrew; Yin, Li
Highlights: Examines the interaction between cyber, relational, and physical spaces using the Splatial framework. Non-polarized vaccination debates were observed in cyber, relational, and physical spaces. Physical space users have a less anti-vaccine stance than relational and cyber space users. Strong interactions are observed between physical–relational, and relational-cyber spaces. Local distance-based clusters exist in relational and cyber space communities. Abstract: With the advent of social media, human dynamics studied in purely physical space have been extended to that of a cyber and relational context. However, connections and interactions between these hybrid spaces have not been sufficiently investigated. The "space-place ( Splatial )" framework proposed in recent years allows capturing human activities in the hybrid of spaces. This study applies the Splatial framework to examine the information propagation between cyber, relational, and physical spaces through a case study of Covid-19 vaccine debates in New York State (NYS). Whereby the physical space represents the regional boundaries and locations of social media (i.e., Twitter) users in NYS, the relational space indicates the social networks of these NYS users, and the cyber space captures the larger conversational context of the vaccination debate. Our results suggest that the Covid-19 vaccine debate is not polarized across all three spaces as compared to that of other vaccines. However, the rate of users with a pro-vaccine stance decreases from physical to relational and cyber spaces. We also found that while users from different spaces interact with each other, they also engage in local communications with users from the same region or same space, and distance-based and boundary-confined clusters exist in cyber and relational space communities. These results based on the Splatial framework not only shed light on the vaccination debates but also help to define and elucidate the relationships between the three spaces. The intense interactions between spaces suggest incorporating people's relational network and cyber presence in physical place-making.